Globalization and health worker crisis: what do wealth-effects tell us? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Owing to lack of relevant data on health human resource (HHR) migration, the empirical dimension of the health-worker crisis debate has remained void despite abundant theoretical literature. A health worker crisis is overwhelming the world. Shortages in health professionals are reaching staggering levels in many parts of the globe. This paper complements existing literature by empirically investigating the WHO hypothetical determinants of health-worker migration in the context of globalization when income-levels matter. In plainer terms, the work explores how the wealth of exporting countries play-out in the determinants of HHR emigration. We assess the determinants of emigration in the health sector through-out the conditional distribution of health human resource emigration. Findings provide very targeted policy implications based on income-levels and existing emigration levels for both physician and nurse worker crises. Beside specific policy recommendations, we also outlined broad policy measures for source-countries, recipient-states and regional (international) institutions.
Keywords: D60; F22; I10; J24; O15; 330; Welfare; Health; Human Capital; Migration